2014
DOI: 10.1128/aem.03198-13
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli O157:H7 Lacking the qseBC -Encoded Quorum-Sensing System Outcompetes the Parental Strain in Colonization of Cattle Intestines

Abstract: The qseBC-encoded quorum-sensing system regulates the motility of Escherichia coli O157:H7 in response to bacterial autoinducer 3 (AI-3) and the mammalian stress hormones epinephrine (E) and norepinephrine (NE). The qseC gene encodes a sensory kinase that autophosphorylates in response to AI-3, E, or NE and subsequently phosphorylates its cognate response regulator QseB. In the absence of QseC, QseB downregulates bacterial motility and virulence in animal models. In this study, we found that 8-to 10-month-old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…coli (42). The decreased colonization by the mraW mutant is less likely due to reduction of motility as less or non-motile E. coli O157:H7 was preferred in the animal intestine including mice (11, 43).…”
Section: Discusssionmentioning
confidence: 99%
“…coli (42). The decreased colonization by the mraW mutant is less likely due to reduction of motility as less or non-motile E. coli O157:H7 was preferred in the animal intestine including mice (11, 43).…”
Section: Discusssionmentioning
confidence: 99%
“…However, Gou et al showed that the absence of qseB resulted in increased bacterial motility but no obvious differences in biofilm formation in E. coli MG1655 (Gou et al 2019). In addition, our results of RT-qPCR showed that inactivation of qseBC resulted in an apparent decrease in the transcript levels of bcsA, csgA, fliC, motA, wcaF and fimA, whereas Sharma and Casey reported that QseBC did not affect the transcription of fliC, and inactivation of qseBC upregulated the transcription of csgA in EHEC O157:H7 (Sharma & Casey 2014). These conflicting results were probably due to the isolation of these E.coli strains from different hosts, and thus the biofilm formation ability and the regulatory mechanisms of biofilm formation might differ between them.…”
Section: Discussionmentioning
confidence: 61%
“…Two-component systems are essential for bacteria to quickly respond and adapt to various environmental stimuli, particularly through changes in target gene transcription (Beier & Gross 2006). In the QseBC two component system, the environmental signal bacterial autoinducer 3 (AI-3) and the mammalian stress hormones epinephrine and norepinephrine (Clarke et al 2006;Hughes et al 2009;Sharma & Casey 2014) are sensed by QseC (an inner membrane-bound sensor histidine kinase (HK)), which initiates a signal transduction cascade that, in many cases, results in the phosphorylation of aspartate residue of QseB (the response regulator (RR)) (Hoch & Varughese 2001;Weigel & Demuth 2016). QseB regulates the transcription of downstream target genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…coli O157:H7 was enumerated in 100 of the swab samples (five per pen; 50 swab samples per treatment) using selective media (Sorbitol-MacConkey agar) and a PCR targeting E. coli O157:H7 virulence genes as per Sharma and Casey (Sharma and Casey, 2014). Approximately 0.3 gm of feces were transferred into enrichment broth (Sharma and Casey et al, 2014) and an aliquot of the broth was plated on sorbitol-MacConkey agar, incubated overnight at 37 o C, and subjected to enumeration by manual counting of nonfermenting colonies the next day. From each pen-specific set of agar plates, 96 colonies were selected and subjected to the PCR targeting E. coli O157:H7 virulence genes.…”
Section: Assessment Of E Coli O157:h7 In the Fecesmentioning
confidence: 99%